CD73 mediated host purinergic metabolism in intestine contributes to the therapeutic efficacy of a novel mesenchymal-like endometrial regenerative cells against experimental colitis - Shao, Bo; Ren, Shao-hua; Wang, Zhao-bo; Wang, Hong-da; Zhang, Jing-yi; Qin, Hong; Zhu, Yang-lin; Sun, Cheng-lu; Xu, Yi-ni; Li, Xiang; Wang, Hao (Frontiers in Immunology, 2023)
Background: The disruption of intestinal barrier functions and the dysregulation of mucosal immune responses, mediated by aberrant purinergic metabolism, are involved in the pathogenesis of inflammatory bowel diseases (IBD). A novel mesenchymal-like endometrial regenerative cells (ERCs) has demonstrated a significant therapeutic effect on colitis. As a phenotypic marker of ERCs, CD73 has been largely neglected for its immunosuppressive function in regulating purinergic metabolism. Here, we have investigated whether CD73 expression on ERCs is a potential molecular exerting its therapeutic effect against colitis. Methods: ERCs either unmodified or with CD73 knockout (CD73-/-ERCs), were intraperitoneally administered to dextran sulfate sodium (DSS)-induced colitis mice. Histopathological analysis, colon barrier function, the proportion of T cells, and maturation of dendritic cells (DCs) were investigated. The immunomodulatory effect of CD73-expressing ERCs was evaluated by co-culture with bone marrow-derived DCs under LPS stimulation. FACS determined DCs maturation. The function of DCs was detected by ELISA and CD4+ cell proliferation assays. Furthermore, the role of the STAT3 pathway in CD73-expressing ERCs-induced DC inhibition was also elucidated. Results: Compared with untreated and CD73-/-ERCs-treated groups, CD73-expressing ERCs effectively attenuated body weight loss, bloody stool, shortening of colon length, and pathological damage characterized by epithelial hyperplasia, goblet cell depletion, the focal loss of crypts and ulceration, and the infiltration of inflammatory cells. Knockout of CD73 impaired ERCs-mediated colon protection. Surprisingly, CD73-expressing ERCs significantly decreased the populations of Th1 and Th17 cells but increased the proportions of Tregs in mouse mesenteric lymph nodes. Furthermore, CD73-expressing ERCs markedly reduced the levels of pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) and increased anti-inflammatory factors (IL-10) levels in the colon. CD73-expressing ERCs inhibited the antigen presentation and stimulatory function of DCs associated with the STAT-3 pathway, which exerted a potent therapeutic effect against colitis. Conclusions: The knockout of CD73 dramatically abrogates the therapeutic ability of ERCs for intestinal barrier dysfunctions and the dysregulation of mucosal immune responses. This study highlights the significance of CD73 mediates purinergic metabolism contributing to the therapeutic effects of human ERCs against colitis in mice.